Restituer les bidonvilles de Nanterre : l’apport d’un outil de visualisation 3D à un projet de sciences sociales - Paul Lecat; Émile Blettery; Lætitia Delavoipière; Frédéric Saly-Giocanti; Sylvaine Conord; Valérie Gouet-Brunet; Alexandre Devaux; Mathieu Brédif; Frédéric Moret (Humanités Numériques)
In the mid-1950s, the first improvised huts for Algerian workers appeared in Nanterre. Soon, these informal shacks grew together and ended up forming urban complexes, presented and administered as shantytowns, and the city of Nanterre was then durably associated with them. This article proposes to review an interdisciplinary research experience around this object of study. Researchers in urban history and sociology collaborated with computer scientists from the IGN in order to use and enrich a platform for spatialisation and visualisation of heterogeneous data to document the history of these shantytowns and to understand the formation and permanence of these places in the current collective memory.